(untitled) (Swiss Medical Weekly, 2020)
BACKGROUND The transition from undergraduate to postgraduate training is a crucial career step for physicians. Several international studies have shown that graduates feel insufficiently prepared to perform various aspects of clinical practice. The publication of a national framework for undergraduate medical education triggered major curricular reforms at our institution. Through this study, we explored the perceptions of preparedness for practice of junior residents who graduated from the new curriculum. METHODS This was a cross-sectional, triangulation mixed-methods quantitative and qualitative study among junior residents and senior physicians of 13 hospitals in western Switzerland. We administered two online questionnaires aimed at exploring perceptions in five areas of clinical competence (knowledge, clinical skills, clinical reasoning, communication and collaboration), as well in self-confidence and coping with the daily work. The qualitative part consisted of six semi-structured focus groups with junior residents, aimed at further clarifying the perceptions and circumstances of their preparedness. Verbatim transcriptions were analysed through thematic analysis. RESULTS Fifty-nine (43.3%) junior residents and 68 (26.5%) senior physicians completed the questionnaire. Among residents, 54.2% considered the curriculum to have adequately prepared them for practice. However, residents felt they were underperforming particularly in developing therapeutic strategies, in communicating with patients’ relatives, and in writing discharge letters. 50.8% (95% confidence interval 37.5-64.1) of them felt overwhelmed by the workload and 39% felt unfulfilled at work. Perceptions of senior physicians about residents’ clinical competences most often agreed with those of their young colleagues. Nineteen residents volunteered to participate in six focus groups. Thematic analysis allowed us to highlight six areas associated with perceptions of underpreparedness: (1) the adequacy of undergraduate instruction; (2) the ability to work efficiently within an interprofessional team; (3) the ability to communicate with patients and colleagues; (4) the effect of the curriculum on the development of critical inquiry and their approach to learning; (5) difficulties in managing their daily clinical work; (6) the negative emotions experienced at the beginning of postgraduate training. CONCLUSIONS Several important aspects of daily clinical practice appear to be insufficiently mastered in the first few months of residency. The resulting stress and anxiety negatively affect job satisfaction. This study provides concrete examples and guidance for program directors and educators on how to better prepare students for postgraduate training.